Letopis Fakultete za gradbeništvo, prometno inženirstvo in arhitekturo 2020/2021 (University of Maribor Press, 2021)
Yearbook Faculty of Civil Engineering, Transportation Engineering and Architecture 2019/2020. The publication presents descriptions of individual courses (with selected student works) for all 4 study programs implemented at the faculties, namely civil engineering, industrial engineering, traffic engineering and architecture. Work in the field of book publishing, excursions, project work and the alumni club are also presented. All diploma and master’s theses of the 2020/2021 academic year are also collected, as well as the activities of the student council.